Analyzing Intraday Financial Data in R: The highfrequency Package - Kris Boudt; Onno Kleen; Emil Sjørup (Journal of Statistical Software)
The highfrequency package for the R programming language provides functionality for pre-processing financial high-frequency data, analyzing intraday stock returns, and forecasting stock market volatility. For academics and practitioners alike, it provides a tool chain required to work with such datasets and to conduct statistical analyses dedicated to spot volatility, jumps, realized measures, and many more. We showcase our implemented routines and models on raw high-frequency data from large stock exchanges.